A checklist of Indian armored spiders (Araneae, Tetrablemmidae) with the description of a new species from the Western Ghats - Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2016)
The Oriental armored spider genus Shearella Lehtinen, 1981 is recorded for the first time from India. Detailed description and illustrations of both sexes of Shearella alii sp. nov. are given. The geographic distribution of the genus is updated. Sinamma sanya (Lin & Li, 2010) is transferred back to Shearella, and Shearella browni (Shear, 1978) back to Monoblemma Gertsch, 1941. A checklist of all Indian tetrablemmid species currently known and a distribution map of all known Shearella spp. are presented.